A Catalog of Interoperability Solutions for Ambient Assisted Living - Duarte, Paulo; Carvalho, Rainara; Viana, Windson (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2024)
As the global population of older adults continues to increase, there is a growing need for innovative technology solutions to improve their well-being and care. One prominent example is the Ambient-Assisted Living (AAL) domain, which involves the connection of many subsystems and heterogeneous devices to offer intelligent services in the user’s living ambient. One of the main challenges in developing AAL systems is the lack of interoperability, which can occur at different levels (from integration between different systems to the semantic level of the data). Although there are several solutions and approaches to this problem, there is no organized body knowledge about interoperability for AAL systems impacting decision making on which approach to use in developing this type of system. This paper proposes a Non-Functional Requirements (NFR) catalog dedicated to interoperability in AAL systems. This catalog establishes relationships among technologic strategies, architectural patterns, platform types, communication protocols, and data semantic and syntactic aspects. We extracted data about interoperability in AAL systems from the academic literature. We identified 25 studies focused on AAL systems prioritizing interoperability as a critical requirement by conducting a systematic mapping followed by a forward snowballing process. We then employed Grounded Theory (GT) to extract information regarding the interoperability characteristics specific to AAL from these documents, finding 41 softgoals and 29 operationalizations. Finally, we validate our findings with two specialists.